The ciam discourse on urbanism, 1928-60 (2007)
In this article, Eric Mumford focuses on CIAM’s discourse tracing the development and promotion of its influential concepts around the notion of the Functional City. By means of a complete analysis of its official documents, as well as of its member’s pronouncements, the author reveals the transformations occurred within the CIAM from its origin at the end of the 1920’s and until its dissolution in 1959. This text is a written version of the lecture given by the professor Mumford on May 7th of 2007 at the seminar Modern Urbanism: from the CIAM to Colombia, organized by the Master Program in Urbanism of the National University of Colombia.